BUDAYA BIROKRASI EWUH PAKEWUH DAN KECURANGAN AKUNTANSI DI PEMERINTAHAN : PERSEPSI APARAT PENGAWAS INTERNAL PEMERINTAH (APIP) INSPEKTORAT KABUPATEN SRAGEN - Ratna Fatmawati (AKTUAL, 2016)
device implementing governance in which APIP is located. APIP position Inspectorate in preventing or uncovering the accounting fraud is very strategic, but in the execution of their duties often appears cheekily to reveal or discover the accounting fraud that occurs if the auditee has a As we know an organization covering culture and structure. During this time more focused on the improvement of the organizational structure rather than the culture contained in the organization. Yet in reality the culture can affect the organizational structure. Cultures were examined in this study is a bureaucratic culture” ewuh-pakewuh” accounting and the accounting fraud that occurred in local government, seeing the possibility of a correlation between a bureaucratic culture with a tendency ewuh-pakewuh accounting fraud. "Ewuh-pakewuh" is one of the culture inherent in the Java community, which in the culture instilled a sense of reluctant, shy and respectful one with the other.Ewuh-pakewuh can occur because of the position, seniority, charisma, as well as good relations that resulted shy and reluctant attitude that against someone. This study aims to determine the perception of the civil servants who served as APIP in the area of culture Inspectorate bureaucracy "ewuh-pakewuh" that occur within the government, especially the regional inspectorate so that it can encourage the emergence of accounting fraud in government agencies. APIP is a Civil Servant is in charge of supervision in a structured and systematic review of the entire dramatically higher positions or more senior. The research method to make a field in Sragen District Inspectorate carried out during 7 (seven) years since 2007 s.d 2014, and supported by interviews with auditors Government Internal Supervisory Apparatus (APIP) in the Inspectorate. And the results showed a bureaucratic culture "ewuh pekewuh" occurred in the APIP Inspectorate Sragen and triggered a government agency accounting fraud. Keyword: Culture ewuh pakewuh, accounting fraud, APIP Inspectorate